Acute effect of propranolol on resting energy expenditure in hyperthyroid patients - Senn, Jaël Rut; Löliger, Rahel Catherina; Fischer, Jonas Gabriel William; Bur, Fabienne; Maushart, Claudia Irene; Betz, Matthias Johannes (Frontiers in Endocrinology, 2023)
Objective: Hyperthyroidism is a common endocrine disorder which leads to higher resting energy expenditure (REE). Increased activity of brown adipose tissue (BAT) contributes to elevated REE in hyperthyroid patients. For rapid control of hyperthyroid symptoms, the non-selective β-blocker propranolol is widely used.While, long-term treatment with propranolol reduces REE it is currently unclear whether it can also acutely diminish REE. Design: In the present prospective interventional trial we investigated the effect of propranolol on REE in hyperthyroid patients. Methods: Nineteen patients with overt primary hyperthyroidism were recruited from the endocrine outpatient clinic. REE was measured by indirect calorimetry before and after an acute dose of 80mg propranolol and during a control period, respectively. Additionally, skin temperature was recorded at eleven predefined locations during each study visit, vital signes and heart rate (HR) were measured before and after administration of propranolol. Results: Mean REE decreased slightly after acute administration of 80mg propranolol (p= 0.03) from 1639 ± 307 kcal/24h to 1594±283 kcal/24h. During the control visit REE did not change significantly. HR correlated significantly with the level of free T3 (R2=0.38, p=0.029)free T4 (R2=0.39, p=0.026). HR decreased 81 ± 12 bpm to 67 ± 7.6 bpm 90 minutes after oral administration of propranolol (p<0.0001). Skin temperature did not change after propranolol intake. Conclusions: In hyperthyroid patients a single dose of propranolol reduced heart rate substantially but REE diminished only marginally probably due to reduced myocardial energy consumption. Our data speak against a relevant contribution of BAT to the higher REE in hyperthyroidism.